Review protocol for a systematic review and meta-analysis on HIV inequities in transgender and non-binary populations - Jennifer Sherwood; Arjee Restar; Don Operario; Hannah Rogers; Ruby Lucas; Ruwenne Moodley; Jessie M. Garcia Gutiérrez; Audren J K Bambilla; Dil Singh; Emerson Dusic; Danielle Giovenco; Shufang Sun (BMJ Open)
Introduction Global disparities in HIV prevalence among transgender women are well documented. However, current epidemiological literature on HIV disparities demonstrates gaps in research that include the diversity within transgender populations—for example, transgender men and non-binary trans people across global regions. This systematic review and meta-analysis protocol aims to summarise global HIV inequities among all transgender and non-binary (trans) populations. The objectives of this review are to estimate pooled HIV prevalence and prevention outcomes (pre-exposure prophylaxis and antiretroviral therapy) and differences by gender identity, global regions and self-report versus lab-confirmed findings among trans adults worldwide.Methods and analysis We will conduct a systematic review of all studies on HIV outcomes among trans youth and adults (aged 15+ years) published between 2000 and 2024, following the Preferred Reporting Items for Systematic Review and Meta-Analysis Prereporting guidelines. We will use Covidence software for the title and abstract screening, full-text review and data abstraction processes. We will summarise the study’s descriptive statistics and conduct meta-analyses of extracted data points to calculate and synthesise pooled findings and effect size. Specifically, we will use the Mantel–Haenszel method with random effects to model our meta-analyses and the DerSimonian and Laird Q test for heterogeneity testing. We will conduct a narrative synthesis on the areas of research that have been conducted to improve HIV prevention and treatment among trans populations and summarise their findings. Subgroup analyses by gender identity, global regions and self-report versus lab-confirmed findings will be conducted.Ethics and dissemination Ethics approval is not applicable for this review since we will not be collecting primary data. The results will be disseminated through peer-reviewed publications and conference presentations.PROSPERO registration number The protocol is registered in the International Prospective Register of Systematic Reviews database (PROSPERO ID: CRD42022357285).